Intention to Quit Smoking in Active Smoking Health Students: What is the Role of Self-Efficacy? - Dwi Anggraini Puspitasari; Rokhmah, Dewi; Iken Nafikadini (Jurnal Promkes: The Indonesian Journal of Health Promotion and Health Education, 2024)
Background: Students were agents of change, meaning they were movers, pioneers, and initiators in driving positive change. Specifically, health students were considered to have high abilities, skills, and knowledge regarding health issues and the dangers of smoking. Each student had different levels of self-efficacy.  Aims: This study aimed to analyze the relationship between self-efficacy and the intention to quit smoking among active smoker health students by involving the dimensions of self-efficacy. Additionally, the researcher described the aspects of self-efficacy dimensions possessed by active smoker health students. Methods: This research was a type of analytical survey research using a quantitative method approach. The population of this study consisted of 60 active smoker health students with the criteria of active S1 health students from the 2016-2018 cohorts. The independent variable in this study was the dimension of self-efficacy, which consisted of the level, strength, and generality dimensions. Meanwhile, the dependent variable was the intention to quit smoking. The research data were collected through interviews and data acquisition tools using questionnaires. Data analysis used univariate and bivariate analysis with the Spearman test. Results: The analysis results of the relationship between respondent characteristics and the intention to quit smoking showed no relationship between respondent characteristics (faculty p=0.609, cohort p=0.928, gender p= -0.925, and age p= -0.673) and the intention to quit smoking. Additionally, the analysis results of the relationship between self-efficacy dimensions (level dimension p=0.000, strength p=0.000, and generality p=0.009) and the intention to quit smoking showed that there was an interrelated relationship affecting the intention to quit smoking. Conclusion: From this research, it can be concluded that there was a relationship between self-efficacy and the intention to quit smoking among health students who are active smokers at the University of Jember.